Implementing Administrative Decentralization in Bobonaro Municipalitytimor-Leste: Human Resource Capacity and Local Governance Challenges - Santos, Adelia dos; Amaral, Adolmando Soares; Martins, Leonito M.; Ramos, Arquimino; Gudinho, Constantinho (Sahabat Publikasi, 2025)
Decentralization has emerged as a critical component of governance reform in developing countries, with the goal of enhancing local accountability, efficiency, and citizen participation. This study examines the implementation of administrative decentralization in Bobonaro Municipality Timor-Leste, focusing on the relationship between human resource capacity and local governance performance. Employing a qualitative case study approach, data were gathered through interviews, observations, and document analysis involving twelve key informants from municipal institutions and local communities. The findings indicate that while legal frameworks establish a robust foundation for decentralization, practical implementation is hindered by institutional weaknesses, fiscal dependency, and misallocation of human resources. Although many local officials possess adequate academic qualifications, deficiencies in merit-based recruitment, technical specialization, and managerial competence prevents effective administration. Additionally, limited citizen participation and gender imbalances detract from accountability in local decision-making processes. The study concludes that successful decentralization necessitates integrated reforms aimed at strengthening institutional capacity, promoting meritocratic governance, and ensuring fiscal autonomy. This research contributes to the literature on post-conflict state-building by illustrating how human resource readiness influences the sustainability and effectiveness of local governance in emerging democracies.